2021
DOI: 10.1093/immadv/ltab006
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs: immune modulators in cancer immunotherapy

Abstract: MicroRNA (miRNA) is a class of endogenous small non-coding RNA of 18–25 nucleotides and plays regulatory roles in both physiological and pathological processes. Emerging evidence support that miRNAs function as immune modulators in tumors. MiRNAs as tumor suppressors or oncogenes are also found to be able to modulate anti-tumor immunity or link the crosstalk between tumor cells and immune cells surrounding. Based on the specific regulating function, miRNAs can be used as predictive, prognostic biomarkers and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 110 publications
0
19
0
Order By: Relevance
“…49 In vitro studies showed that blockade of miR-15a/16-1 decreased the expression of TIM-3, LAG-3 and PD-1 and enhanced functional CD8 + T cells by increasing the expression of mTOR signalling pathway. 49,50 These findings suggest that miR-15a/16-1 as biomarkers of resistance to ICIs in glioma and potential therapeutic targets for improving the sensitivity to ICIs. An interesting study investigated the role of adenosine deaminase acting on RNA-1 (ADAR1) in melanoma immunomodulation.…”
Section: 1mentioning
confidence: 88%
“…49 In vitro studies showed that blockade of miR-15a/16-1 decreased the expression of TIM-3, LAG-3 and PD-1 and enhanced functional CD8 + T cells by increasing the expression of mTOR signalling pathway. 49,50 These findings suggest that miR-15a/16-1 as biomarkers of resistance to ICIs in glioma and potential therapeutic targets for improving the sensitivity to ICIs. An interesting study investigated the role of adenosine deaminase acting on RNA-1 (ADAR1) in melanoma immunomodulation.…”
Section: 1mentioning
confidence: 88%
“…miRNAs regulate many immune-tumor cell junctions and essential immune response processes ( 178 ). miRNAs have also been discovered to be tumor suppressors or oncogenes, with the ability to control antitumor immunity or crosstalk between cancer cells and their surrounding immune cells ( 179 ). miRNAs can be used as prognostic, diagnostic, and targeted immunotherapeutics based on their specific regulatory role.…”
Section: Role Of Mir-128 In Immune Responses and Immunotherapy In Cancermentioning
confidence: 99%
“…As described above, miRNAs play key roles in tumor immunity through their functions in both tumor and immune cells, highlighting their potential in disease classification and as therapeutic agents ( 301 ). Various classes of immunotherapy were shown to impact the miRNA networks in the TME ( 302 304 ). In this section, we will highlight the involvement of miRNAs in immunotherapy action mechanisms and discuss opportunities to improve clinical outcomes.…”
Section: Mirnas and Cancer Immunotherapymentioning
confidence: 99%